Disparity in the Application of Legal Rules to Gambling Crimes Through Electronic Media - Musriko Musriko; Febriansyah Febriansyah (Faculty of Law, Universitas Pekalongan, 2023)
Gambling is a betting game in which a value that is considered valuable is wagered in advance. Gambling is a criminal offense, of the many online gambling cases that have been decided by the court, including Decision Number 111/Pid.Sus/2021/Pn Unr, and Decision Number 139/Pid.Sus/2021/Pn Skb. Both decisions are decisions related to gambling crimes committed through electronic means, but from the two decisions, there are fundamental differences, especially related to the application of the reason is, where in the first decision the Judge used Article 303 of the Criminal Code, but in other decisions, the judge used the ITE law. Based on that, this study will examine why there is a disparity between the two decisions above. This study uses a normative juridical method with a legislative approach and a case approach. The results of the study show that even though the actions of the two defendants were both carried out with electronic media facilities (smartphones) belonging to each defendant, the judge in making a verdict, tended to follow the demands of the Public Prosecutor. Disparity in the application of law in practice can result in disruption of the value of legal certainty and justice.